Echoes of Leibniz in Pope’s Essay on Man: Criticism and Cultural Shift in the Eighteenth Century - Sierra Billingslea (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
This paper is an examination of the intellectual relationship between Alexander Pope’s An Essay on Man and the philosophy of Gottfried Wilhelm Leibniz. This relationship was accentuated by Crousaz, a Swiss critic, who accused Pope of plagiarizing Leibniz’s misguided philosophy due to the evidence of Leibniz’s Principle of the Best, Principle of Sufficient Reason, and Principle of Continuity found within An Essay on Man. This paper argues that both Leibniz and Popes’ philosophies do not reflect a direct relationship but instead share the spirit of Augustan thought as well as a similar classical upbringing. Crousaz and other critics who criticized the philosophical constructs in the poem, particularly Voltaire, express the drastic social changes that took place around the turn of the century in Europe — a sudden questioning of faith and classical learning brought on by both political changes and natural disaster. In this way, An Essay on Man and the related criticism act as a microcosm of the changing ideals of the Augustan Age as it passed into the Enlightenment.
Keywords: Leibniz; Alexander Pope; Criticism; Philosophy; Eighteenth Century; Enlightenment; Crousaz; Voltaire; The Spectator